Cuestión indígena en la América independiente - Jancsó, Katalin (Acta Hispanica, 2011)
The aim of this study is to present the political, economic and social circumstances that had aninfluence on the situation of Latin-American indigenous people after the wars of independence of thefirst decades of the nineteenth century. It describes what movements have risen during the last twocenturies, what kinds of ideobgies were born to solve the indigenous problem and how the first privateindigenous associations were established. It also examines the appearance of the institutionalization ofindigenismo into official government policies and gives a brief view of the present legal regulation of thequestion in the region.